A popular reform in a subject commune: the Moncalieri estimo of 1351 (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
In this essay, I aim to analyze the 1351 estimo of the commune of Moncalieri, the result of a fiscal reform developed by the local popular party, and which represents a unicum in the unpublished and particularly rich fiscal sources of the commune of Moncalieri. To better understand the exceptionality of the 1351 fiscal records, the article reconstructs the political framework in which the decision to produce the estimo matured: the affirmation of the popular party was decisive, imposing at the center of the political debate the fairness of taxation and a greater control over the territory and people. The article then explores the complex documentary system made up of the various tax registers produced during the estimation operations, which involved analytical surveys of the territory conducted by public officials. This double analysis, of the political context of production and of the administrative-documentary practices, makes it possible to highlight the strong political nature of the tax document, the outcome (and the sign) of an ambitious popular political project.
Keywords: 14th century; Popolo; taxation; documentary practices